DNA methylation changes in CD4+ T cells isolated from multiple sclerosis patients on dimethyl fumarate. Issue 3 (July 2018) - Maltby, Vicki E; Lea, Rodney A; Ribbons, Karen A; Sanders, Katherine A; Kennedy, Daniel; Min, Myintzu; Scott, Rodney J; Lechner-Scott, Jeannette
Background: Dimethyl fumarate is an oral treatment for multiple sclerosis, whose mechanism of action is not fully understood. Objective: To investigate the effects of dimethyl fumarate on DNA methylation in the CD4 + T cells of multiple sclerosis patients. Methods: We performed Illumina EPIC arrays to investigate the DNA methylation profiles of CD4 + T cells derived from multiple sclerosis patients before and after dimethyl fumarate treatment. Results: Treatment with dimethyl fumarate resulted in 97% of differentially methylated positions showing hypermethylation. Four genes, SNORD1A, SHTN1, MZB1 and TNF had a differentially methylated region located within the transcriptional start site. Conclusion: This study investigates the effect of dimethyl fumarate on DNA methylation in multiple sclerosis patients.